IMPROVED MATHEMATICAL LEARNING RESULTS OF OPERATING MATERIALS CALCULATE FRACTIONAL NUMBERS THROUGH ETHNOMAMATIC LEARNING GEJOH LESUNG IN CLASS V STUDENTS NGABEAN PONJONG ELEMENTARY SCHOOL STUDENTS - Ganis Nurma Febriarti; Dika Wulandari; Erna Nuryani; Maisaroh Farida Nurrohmah; Mimin Nurnaini Zumaroh (Universitas PGRI Yogyakarta, 2022)
Ethnomamatics that associates culture and mathematics certainly have characteristics that support each other. In this paper discussed about how ethnomamatics is appliedto mathematics learning, by associating existing cultural products with the content or concepts of mathematics studied. By looking at various ways of associating culture and mathematics in ethnomamatics, it is characterized by ethnomatteric characteristicsin mathematics learning, especially in learning in schools. This research aims to find out: (1) the learning process of Ethnomamatics Gejoh Lesung on the operating material of calculating fractional fractions of class V in SDN Ngabean Ponjong Gunungkidul Regency, (2) whether the results of learning fractional calculation operating materials can be leveledn through ethnomatematics learning in class V SDN Ngabean Ponjong Gunungkidul Regency. This research instrument is (1) learning outcome tests, (2) student activity observation sheets, (3) observation sheets of learning implementation, and (4) student response questionnaires. Data is analyzed using descriptive analysis. The results showed that: (1) student activity in Ethnomamatics learning Gejoh Lesung based on observations. In cycle II is better because it is in the category of